Fake News or Weak Science? Visibility and Characterization of Antivaccine Webpages Returned by Google in Different Languages and Countries - Arif, Nadia; Al-Jefri, Majed; Bizzi, Isabella Harb; Perano, Gianni Boitano; Goldman, Michel; Haq, Inam; Chua, Kee Leng; Mengozzi, Manuela; Neunez, Marie; Smith, Helen; Ghezzi, Pietro (Frontiers in Immunology, 2018)
The 1998 Lancet paper by Wakefield et al , despite subsequent retraction and evidence indicating no causal link between vaccinations and autism, triggered significant parental concern. The aim of this study was to analyse the online information available on this topic. Using localized versions of Google, we searched “autism vaccine” in English, French, Italian, Portuguese, Mandarin and Arabic and analyzed 200 websites for each search engine result page (SERP). A common feature was the newsworthiness of the topic, with news outlets representing 25-50% of the SERP, followed by unaffiliated websites (blogs, social media) that represented 27-41% and included most of the vaccine-negative websites. Between 12% and 24% of websites had a negative stance on vaccines, while most websites were pro-vaccine (43-70%). However, their ranking by Google varied. While in Google.com the first vaccine-negative website was the 43rd in the SERP, there was one vaccine-negative webpage in the top 10 websites in both the British and Australian localized versions and in French and two in Italian, Portuguese and Mandarin, suggesting that the information quality algorithm used by Google may work better in English. Many webpages mentioned celebrities in the context of the link between vaccines and autism, with Donald Trump most frequently. Few websites (1-5%) promoted complementary and alternative medicine (CAM) but 50-100% of these were also vaccine-negative suggesting that CAM users are more exposed to vaccine-negative information. This analysis highlights the need for monitoring the web for information impacting on vaccine uptake.